Sirtuin SIRT6 suppresses cell proliferation through inhibition of Twist1 expression in non-small cell lung cancer - Han, Zhijun (e-Century Publishing Corporation, 2014)
SIRT6 is a member of the NAD(+)-dependent class III deacetylase sirtuin family. Current studies have revealed that SIRT6 plays important roles in the epigenetic regulation of genes expression and contribute to the proliferation, differentiation and apoptosis of cancer cells. However, the biological function of SIRT6 in lung cancer has not been elucidated. The present study showed that the mRNA and protein levels of SIRT6 were decreased in human non-small cell lung cancer (NSCLC) tissues and cell lines. MTT assay showed that overexpression of SIRT6 could inhibit the proliferation in NSCLC cells. In contrast, SIRT6 knockdown using small interfering RNA promoted NSCLC cells proliferation. On the molecular level, we found that SIRT6 inhibited the expression of Twist1 both at the mRNA and protein levels in NSCLC cells. Taken together, these results demonstrated for the first time that SIRT6 suppressed NSCLC cells proliferation via down-regulation of Twist1 expression and might provide novel therapeutic targets in the treatment of lung cancer.